Design and Development of a Web-Based E-Learning System at SMA Tri Dharma Palembang - Ayu, Niken; Supratman, Edi (Information Technology and Science (ITScience), 2025)
The rapid advancement of information and communication technology has transformed learning practices globally, yet teaching activities at SMA Tri Dharma Palembang remain predominantly conventional and do not fully align with the requirements of the Merdeka Curriculum. This study was conducted to design and develop a web-based e-learning system that integrates learning material management, assignment submission, automated and manual assessments, discussion forums, and real-time student activity monitoring. The research applied a Research and Development (R&D) approach consisting of needs analysis, system design using Unified Modeling Language (UML), implementation with PHP, MySQL, and Bootstrap, and evaluation through black box testing and a Likert-scale user satisfaction survey. The system was tested by two teachers and ten students, and expert validation was conducted to assess the research instrument. Results show that all modules performed as expected during functional testing, and the user satisfaction survey yielded an overall score of 85.33%, categorized as very good. The findings were analyzed using the Technology Acceptance Model (TAM), the Unified Theory of Acceptance and Use of Technology (UTAUT), and the DeLone & McLean IS Success Model, confirming that system quality, ease of use, usefulness, and user satisfaction significantly influence e-learning adoption in secondary education. This study contributes theoretically by extending the application of established information systems success models in the Indonesian school context and practically by providing a digital platform that supports the implementation of the Merdeka Curriculum. Keywords: activity monitoring; e-learning; Merdeka Curriculum; TAM; UTAUT